Managing the repatriation of professionals following overseas assignment - Burns, Graham (2017)
Despite decades of research about culture shock, and latterly but not to the same extent, reverse culture shock, it seems that little is understood about how to manage the process of repatriation after an overseas assignment in the commercial world. Attrition rates of repatriates leaving their employers within the first year following their return continue to rise as those individuals consistently report feeling undervalued by their employers.